A Monetary History of the Ottoman Empire - Pamuk, Seevket (Cambridge university, 2013)
This book is about money and empire and their place in the world economy at the dawn of the era of capitalism. In its approach and focus, I have been inspired by the insistence of a number of ®ne historians in recent decades,most notably Fernand Braudel, my former teacher Carlo Cipolla,V. Magalhaes-Godinho, Peter Spufford, and Pierre Vilar, that monetary history needs to be painted on a large canvas. The strong, two-way interaction between long-distance trade, specie ¯ows, and money makes the adoption of a global perspective essential for understanding both the Middle Ages and the Early Modern period. This is especially the case for the monetary history of a large empire located at the crossroads of intercontinental trade, always vulnerable to the vicissitudes of commerce,payments, and monetary ¯ows. Monetary history thus offers us the opportunity to transcend the compartmentalized approach of so many historians and emphasize the linkages between the history of the Eastern Mediterranean, or the Near East for the lack of a better term, and those of Europe and South Asia over a period of six centuries.